Analysis of anthocyanin colour stability from fruits of Ixora siamensis / Nur Amirah binti Mat Nor - Mat Nor, Nur Amirah (2012)
This studies are to identify the potential of fruits from Ixora siamensis (“pokok jejarum”) as a new source of antocyanin natural colourant and to evaluate the suitability of the anthocyanin natural colourant with ferulic acid (FA) stabilizing agent when blended with poly(vinyl) alcohol (PVA) to form a coating system. Furthermore, the aim is to analyse colour stability of anthocyanin colourant in a coating system in terms of pH and co-pigmentation under UV-B exposure by CIE colour system. The natural anthocyanin colourant from Ixora siamensis was extracted by using acidified methanol for crude extraction. Further purification of crude extraction was performed by using liquid-liquid partition extraction and ion exchange column chromatography. Different proportions of ferulic acid as stabilizing agent were added in order to improve and enhance the resistance towards the UV-B irradiation during exposure period. FA added colourant was mixed with PVA to develop coating system. To test the colour stability of crude and purified anthocyanin colourant and anthocyanin-PVA blend towards UV-B irradiation, CIE colour analysis was conducted. CIE results obtained were analysed in terms of L* C* Hº a* b* colour coordinate values. Total colour difference (ΔE) and saturation (s) of colour were determined in order to evaluate the visual colour variation. Based on the results obtained, the colour of the untreated anthocyanin colourant and anthocyanin-PVA blend was susceptible to UV degradation during 93 days of exposure. The addition of 2% FA at pH 3 performed better colour stability. CIE results also showed that the colour variation of anthocyanin and anthocyanin-PVA blend definitely influenced by pH variation.